Escarpas rochosas e pinturas na Serra de Passos/Sta Comba (Nordeste de Portugal) - Sanches, Maria de Jesus (2016)
This paper will present the most extensive set of sites displaying post-glacier pre-historic rock paintings located in the Portuguese territory, specifically in the Serra de Passos/Sta Comba area of Northeastern Portugal. There, in Regato das Bouças during the passage of the 1980s to the 1990s, a wide group of sites had already been identified; they were recorded using decalcs over plastic and were classified as Public Interest Real Estate (a Portuguese Heritage classification). Since the beginning of archaeological survey by the current team in 2010, many other shelters displaying schematic painting were found. Given the scientific necessity of its divulgence the following article will focus on the distribution, spatial and topographic analysis of these painted surfaces as well as the divulgence of the recordings made by plastic decals during the 1990s. It will present a brief description of the new shelters that will be shown here through photographs. It will also present a briefed general analyse of this set of prehistoric paintings that we can already name as the Portuguese Batuecas.